Determinan Penyaluran Kredit pada Bank Perkreditan Rakyat di Sulawesi Utara - Roring, Gaby Dainty Julliet; Parasan, Pradipta M.; Mawitjere, Patricia S.; Lambut, Adventinus K. (CV. Kurnia Grup, 2024)
The role of banking as an intermediation institution is very important in supporting the running of the economy and national development, considering its function as an organizer of payment transactions, an intermediary between debtors and creditors, and so on. The main focus and activity of banking in carrying out its intermediation function is credit distribution. This research is motivated by the existence of a gap phenomenon where the credit distributed by Rural Banks in North Sulawesi is not yet optimal. Thus, it is necessary to examine the factors that influence credit distribution, some of which are Third Party Fund (TPF) and Non-Performing Loan (NPL). The aim of this research is to find out the influence of Third Party Fund and Non-Performing Loan on credit distribution at Rural Banks in North Sulawesi. The analysis technique used in this research is multiple linear regression with the Ordinary Least Square (OLS) method. The results show that Third Party Fund and Non-Performing Loan have a positive and significant effect on credit distribution. Based on the results, it is hoped that Rural Banks can further increase Third Party Fund and minimize the occurrence of Non-Performing Loan in order to increase credit distribution at Rural Banks in North Sulawesi.